2018
DOI: 10.1002/aoc.4622
|View full text |Cite
|
Sign up to set email alerts
|

Engineered mesoporous ionic‐modified γ‐Fe2O3@hydroxyapatite decorated with palladium nanoparticles and its catalytic properties in water

Abstract: A new mesoporous organic-inorganic nanocomposite was formulated and then used as stabilizer and support for the preparation of palladium nanoparticles (Pd NPs). The properties and structure of Pd NPs immobilized on prepared 1,4-diazabicyclo[2.2.2]octane (DABCO) chemically tagged on mesoporous γ-Fe 2 O 3 @hydroxyapatite (ionic modified (IM)-MHA) were investigated using various techniques. The synergistic effects of the combined properties of MHA, DABCO and Pd NPs, and catalytic activity of γ-Fe 2 O 3 @hydroxyap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…The magnetic property of FeS x -Fe 2 O 3 @CN-8 was measured by the Quantum Design SQUID MPMS-XL7 magnetometer. As shown in Figure 6a, the magnetic hysteresis loop for developed FeS x -Fe 2 O 3 @CN-8 catalyst exhibits a saturated magnetization of 10.4 emu g À1 at 5,500 Oe at 293 K. [63,64] As shown in Figure 6a inset, the FeS x -Fe 2 O 3 @CN-8 catalyst could also be easily separated by an external magnet and reused after thoroughly washed with ethanol, further supporting above the magnetic analysis. [65] The recyclability test (Figure 6b) suggested that FeS x -Fe 2 O 3 @CN-8 catalyst could be consecutive reused for five times without obvious loss of activity.…”
Section: Reusability Of Fes X -Fe 2 O 3 @Cn-8 Catalystmentioning
confidence: 99%
“…The magnetic property of FeS x -Fe 2 O 3 @CN-8 was measured by the Quantum Design SQUID MPMS-XL7 magnetometer. As shown in Figure 6a, the magnetic hysteresis loop for developed FeS x -Fe 2 O 3 @CN-8 catalyst exhibits a saturated magnetization of 10.4 emu g À1 at 5,500 Oe at 293 K. [63,64] As shown in Figure 6a inset, the FeS x -Fe 2 O 3 @CN-8 catalyst could also be easily separated by an external magnet and reused after thoroughly washed with ethanol, further supporting above the magnetic analysis. [65] The recyclability test (Figure 6b) suggested that FeS x -Fe 2 O 3 @CN-8 catalyst could be consecutive reused for five times without obvious loss of activity.…”
Section: Reusability Of Fes X -Fe 2 O 3 @Cn-8 Catalystmentioning
confidence: 99%
“…[11] Some MNPs that used in catalytic applications include iron oxide (Fe 3 O 4 ), cobalt ferrite (Fe 2 CoO 4 ), maghemite ( γ -Fe 2 O 3 ), and zinc ferrite (ZnFe 2 O 4 ). [12][13][14][15] Today, great attention has been paid to cobalt ferrite (CoFe 2 O 4 ) nanocrystals with spinel structure due to their superior characteristics, such as high saturation magnetization, large surface area-tovolume ratio, and shape-dependent magnetic behavior. [16][17][18][19][20][21][22] As a review of previous studies, many functionalized CoFe 2 O 4 MNPs have been reported as a heterogeneous catalyst in multicomponent reactions (MCRs) such as CoFe 2 O 4 @SiO 2 @CPTMS, [13] CoFe 2 O 4 @SiO 2 -SO 3 H, [23] CoFe 2 O 4 @SiO 2 -PTA, [24] CoFe 2 O 4 /TMU-17-NH 2 , [25] CoFe 2 O 4 @l-asparagine-Cu/ Ni, [26] CoFe 2 O 4 @glycine-M, [27] CoFe 2 O 4 @Pr.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the so‐called water phase reactions were performed with the aid of organic solvents, such as DMF–H 2 O, CH 3 CN–H 2 O, or EtOH–H 2 O . Although there are a few reports of the Mizoroki–Heck reaction in neat water, these catalytic systems usually suffer from at least one of the following shortcomings: the need for complicated and/or toxic ligands; the use of surfactants or phase transfer catalyst to improve solvation of the organic substrate; the need for complicated and/or toxic ligands; and the lack of reusability. In past decades, many efforts have been made to solve these problems through the development of active, reusable catalysts and more facile and benign procedures, but satisfactory solutions are still a challenge.…”
Section: Introductionmentioning
confidence: 99%